2010
DOI: 10.1094/cchem-04-10-0059
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Jet Cooking and pH on Extraction and Molecular Weight of β‐Glucan and Arabinoxylan from Barley (Hordeum vulgare Prowashonupana)

Abstract: Cereal Chem. 87(6):607-611

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…The 'Esmeralda' malting barley has a pericarp thickness of ≈106 µm; the feed barleys have a higher thickness than the barley; 'Pastor Ortiz' has ≈280 µm. This data agrees with the reports that good malting barley usually has a thinner husk than feed barley (Figueroa, 1985;Rose et al, 2010). The thickness of the layers calculated from the ESEM microphotograph (Fig.…”
Section: Husk and Bran Microstructuralsupporting
confidence: 91%
See 1 more Smart Citation
“…The 'Esmeralda' malting barley has a pericarp thickness of ≈106 µm; the feed barleys have a higher thickness than the barley; 'Pastor Ortiz' has ≈280 µm. This data agrees with the reports that good malting barley usually has a thinner husk than feed barley (Figueroa, 1985;Rose et al, 2010). The thickness of the layers calculated from the ESEM microphotograph (Fig.…”
Section: Husk and Bran Microstructuralsupporting
confidence: 91%
“…This interest arises from the evidence that β-glucan is an essential supplement in human nutrition that reduces the risk of cancer and diabetes and assists in the prevention of obesity and cholesterol levels (Pino, et al, 2021;Roudi et al, 2017;Schlörmann and Glei, 2017). Rose et al (2010) indicated that the benefits of barley β-glucans are related to concentration within the grain and the processing conditions that may affect the extractability and molecular weight. In this context, microwave energy can modify the kernel endosperm in seconds and increase the industrial quality of grains.…”
Section: Introductionmentioning
confidence: 99%
“…The 'Esmeralda' malting barley has a pericarp thickness of ≈106 µm; the feed barleys have a higher thickness than the barley; 'Pastor Ortiz' has ≈280 µm. This data agrees with the reports that good malting barley usually has a thinner husk than feed barley (Figueroa, 1985;Rose et al, 2010). The thickness of the layers calculated from the ESEM microphotograph (Fig.…”
Section: Husk and Bran Microstructuralsupporting
confidence: 91%
“…Knuckles et al (1997) reported that the β-glucan molecular weight decreased as the water temperature of extraction increased from 25, 65°C to 100°C. Rose et al (2010), indicated that food processing conditions might affect the extractability and molecular weight of β-glucans and arabinoxylans in cereal products.…”
Section: Effect Of Microwave Heating On β-Glucan and Dietary Fibermentioning
confidence: 99%
See 1 more Smart Citation